MENGGALI POTENSI KEKAYAAN MOTIF BATIK MODERN PERKUMPULAN BATIK SIDO LUHUR PAKUALAMAN YOGYAKARTA - Muafi Muafi; Muchammad Sugarindra; Endar Abdi Prakoso (LP2M Universitas Hasanuddin, 2020)
Exploring the Potential Wealth of Modern Batik Motif Sido Luhur Pakualaman Batik Association YogyakartaAbstract. Sido Luhur Pakualaman Batik Association has a unique batik motif that is Mount Ketur motif. The Mount Ketur motif comes from historical values in the Pakualaman community. The historical value which is embodied in the batik motif is one of creativity forms from the craftsmen for their intellectual property. Each motif formed from each batik craftsman has extraordinary potential in terms of beauty, local wisdom, and meaning of life. Batik motifs become a very decisive element because from the motif, we will know whether batik has a